Analisis Semiotika Representasi Budaya Lokal dalam Film Pendek Jangan dipendam Sendiri pada Kanal YouTube Gemericik - Ghoitsa Chavilla Hafshoh; Suryati Suryati; Muzaiyanah Muzaiyanah (Journal of Innovative and Creativity, 2026)
The development of digital media, particularly YouTube, has created new spaces for the representation and preservation of local culture through audiovisual works. The short film Jangan dipendam Sendiri, published on the Gemericik YouTube channel, utilizes digital media to present the Besemah language and cultural values of Pagaralam City. This study aims to analyze how local cultural representation is constructed in the film through the use of the Besemah language and the accompanying social values. This research employs a descriptive qualitative approach using Roland Barthes’ semiotic analysis. The research object is the audiovisual text of the short film Jangan dipendam Sendiri, with data collected through film text observation, documentation, and supporting interviews. The data were analyzed using the stages of denotation, connotation, and myth to reveal the cultural meanings represented in the film. The findings indicate that local culture is predominantly represented through the use of the Besemah language in inter-character dialogues, as well as through values of solidarity, care, and social kinship. This representation is not merely linguistic but also constructs cultural myths of togetherness and social concern within the Besemah community. This study concludes that digitally based short films play an effective role as a medium for representing and preserving local culture amid globalization, while also contributing to the enrichment of visual communication and local cultural studies.